Newly derived children-based food index. An index that may detect childhood overweight and obesity. (18th August 2015) - Magriplis, E.; Farajian, P.; Risvas, G.; Panagiotakos, D.; Zampelas, A.
Abstract: A food index (FI) based on a priory knowledge was developed to assess the role of diet on overweight (OW) and obesity (OB) in school-aged children. This included «positive» and «negative» foods based on research evidence and food guidelines, with scores set accordingly. Statistical tests were used to strengthen the sensitivity of the index. The FI was validated using data from the GRECO study. The score ranged from 17 to 53.5 (mean 34.8 ± 5.01) and was inversely associated with body mass index (BMI) (−0.057 ± 0.02; 95% CI −0.098, −0.017) and waist circumference (WC) (−0.08 ± 0.03, 95% CI: −0.137, −0.022). Associations remained significant upon adjusting for age, gender and physical-inactivity ( p = 0.02 ad 0.013, respectively). When stratified by gender, the association between FI and WC was not significant for boys ( p = 0.08). The association with BMI remained significant for females and males ( p = 0.047 and 0.037, respectively). The derived FI seems a valuable tool in detecting OW in children.